Influence of excessive body weight on cancer development and prognosis - Bielak, Alicja; Gryta, Jakub; Iwan, Karolina; Janczewska, Martyna; Kalicka, Maria; Krysa, Tomasz; Kolasa, Agata; Radziejowska, Zuzanna; Szklarz, Magdalena; Kutermankiewicz, Jan (Quality in Sport, 2023)
Introduction and purpose According to the WHO, overweight and obesity are defined as excessive or abnormal accumulation of adipose tissue, leading to deterioration of health. Excessive body weight is a constantly growing public health problem that has reached the scale of a pandemic. Currently, there is ample evidence that excess body weight increases the risk of developing cancer and worsens the prognosis. The aim of this review is to analyze the impact of overweight and obesity on cancer development and prognosis, and to elucidate pathogenesis. State of knowledge Based on the current state of knowledge in epidemiology, it is estimated that approximately 20% of all malignancies are related to excessive body weight. So far, there is sufficient evidence to support an association between excess body fat and 13 out of 24 cancer sites: esophagus, gastric cardia, colon, liver, gallbladder, pancreas, postmenopausal breast, endometrium, ovary, kidney, meningioma, thyroid and multiple myeloma. Adipose tissue cells produce growth factors, hormones and cytokines that can interfere with the regulation of cell growth and survival. Excess adipose tissue leads to systemic chronic inflammation, oxidative stress, insulin resistance, hyperinsulinemia, increase in sex hormones, increase in leptin levels and a decrease in adiponectin levels. This leads to DNA defects, stimulation of angiogenesis, cell proliferation and inhibition of apoptosis, and thus promotes the development of cancer. In addition, studies have estimated that excess body weight is responsible for 14% of cancer deaths in men and 20% in women. Conclusions Due to the increasing problem of obesity and cancer worldwide and the proven causal relationship between these diseases, it is necessary to intensify nutrition education and promote a healthy lifestyle in order to minimize excessive body weight, and thus reduce the incidence of cancer.